PHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY OF BERKHEYA BERGIANA LEAVES - Odeleye, O.; Oyedeji, A.; Opoku, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The use of medicinal plants in the world and especially in South Africa, contributes significantly to primary health care. The genus Berkheya belongs to the family of the Asteraceae. There are about 75 species of Berkheya. 71 species are widespread in Southern Africa and 30 species are spread in Natal. The plant material was air-dried, powdered and extracted with methanol. The fractions were obtained by successive extraction to yield n-Hexane (Hex), Chloroform (CHCl3), Ethyl acetate (EtOAc), and n-Butanol (BuOH). Phytochemical screening was carried out using standard methods. The antioxidant activity was investigated by DPPH radical scavenging effect, by reducing power, by the metal Chelating effect on ferrous ion and by the ABTS scavenging effect. Phytochemical screening carried out on B. bergiana revealed the presence of carbohydrates, flavonoids, terpenoids, saponins and tannins, but the absence of anthraquinones and alkaloids. The result demonstrated that the methanol extract of B. bergiana had excellent antioxidant activities and also showed that the crude extract and fractions were found to have different levels of antioxidant activity in all the systems tested. Results revealed that the BuOH fraction exhibited the best performance in DPPH and the Metal chelating assay, 93.7% and 63.0% respectively. IC50’s were determined for the fractions and EtOAc showed the lowest IC50 (110.73 µg QE/mg) Total phenolic, proanthocyanidins and flavonoid contents in the crude extract and the fractions were also determined. The EtOAc fraction (12.29+0.11GAE mg g-1) had the highest total phenolic content. A strong correlation was recorded between DPPH/GAE (R2= 0.85). This study of phytochemical characteristics and antioxidant activity of the methanol extract and the fractions of B. bergiana was being conducted for the first time. Acknowledgements: National Research fund (NRF), University of Zululland research committee.